PENGARUH KEBIJAKAN MODAL KERJA TERHADAP PROFITABILITAS PADA PERUSAHAAN HOTEL DAN RESTORAN DI BURSA EFEK INDONESIA - Yuliati, Ni Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2013)
ABSTRACT The company’s main objective is to maximize prosperity for shareholders. Working capital is a part of resources that can have a direct impact on company’s profitability. This study is aimed at determining the effect of policy of working capital on profitability in the Hotel and Restaurant companies listed in Indonesian Stock Exchange. The  variables consists of assets structure, working capital turnover, liquidity and financial of working capital. The population in this study all the hotel and restaurant companies listed in Indonesian Stock Exchange there were 16 companies with periode of 2008-2011. Those companies serve as population to the applied method of census. The technique of analysis used was the multiple linier regression which testing the effects between independent variables and dependent variable. The results of this study were 1) Assets structure has significant positive effect on profitability; 2) Working capital turnover has significant positive effect on profitability; 3) Liquidity has  no significant effect on profitability; 4) Financial of working capital has no significant effect on profitability; and 5) Working capital simultaneously has significant effect on profitability. Keywords : assets structure, working capital turnover, liquidity, financial of working capital and profitability